HIV-2 infection and chemokine receptors usage - Clues to reduced virulence of HIV-2 - Azevedo-Pereira, JM (2015)
Human immunodeficiency virus type 1 (HIV-1) and type 2 (HIV-2) are the causative agents of Acquired Immunodeficiency Syndrome (AIDS). Without therapeutic intervention, HIV-1 or HIV-2 infections in humans are characterized by a gradual and irreversible imm